Método de muestreo para abeja solitaria Hymenoptera Megachilidae (Lorraine 1810)” - Fajardo García, Marillina Nerlandesa (2022)
The bees of the genus Hymenoptera Megachilidae are solitary bees, as their name indicates, they spend alone, these are the ones that do not produce honey, they usually make their nests in the ground or trunk, another characteristic of this species is that their behavior is docile, they do not sting. The nests of solitary bees are made up of several cells, most of them are females and these do not have contact with their young, they make their nest with the pollen they gather to feed their young and they are pollinators. Solitary bees (Hymenoptera: Megachilidae) serve farmers as biological control due to their habit, the same ones that are in an accelerated process of disappearance, due to chemical control practices carried out by man. The solitary bee belonging to the Megachilidae family are carpenter bees make their nests in firewood; mason bees make their nest in cane or log; leafcutter bees collect leaves; Digger bees make their nests on the ground. The methods for capturing these solitary bees are artificial nests (cane); Artificial nest with a single material and diameter; Artificial nest (cane, wood and bamboo) and nest built with pieces of leaves, but the appropriate method was detected and the most used is the cane nest.